Um olhar reflexivo sobre o olhar prático: a visão dos cursistas do curso Mídias na educação para formação de professores - Muñoz, Cleide Maria dos Santos (2011)
This project arose out of a need to answer to some questions: why is there still a gap between the teacher and the student in the teaching-learning process? Why is the society still so critical about education? What is the real problem? Having no ambition to answer these questions completely, but thinking of some possible solutions, this research was conducted in order to find out whether or not teachers are able to take advantage of the courses, apply what they had been taught, and, if they are not, why it happens. It is important to know how teachers feel about this process, which is ambiguous, and sometimes contradictory, but always mobilizing and enlightening. For this matter, the aim of this project is to analyse how profiting the training courses are and, more specifically, a) to analyse the discourse of the teachers who work at the Digital Media and Education Course; b) to speculate on the connection between the teacher s discourse and the demands of the new century. This research led to the consideration of the following hypothesis: to understand the reason why education is seen as poor and insufficient in the eyes of society despite the many training/development courses that are offered, it is essencial that we understand how teachers feel in this context who, where, and when. Consider who - students of the Digital Media and Education Course; where - the course itself; and when the 21st century, based on the report of International Commission on Education for the Twenty-first Century (UNESCO). The justification for the study is that its results may significantly contribute to the elaboration of new programmes for teacher s training courses